From seeds of change to harvesting equality: Women in India’s agro-ecology based agri-food systems - Singh, Sonali (International Food Policy Research Institute, 2023)
The Indian agricultural system is undergoing rapid degradation because of climate-induced shocks and stressors. As a result, there have been endeavors among governments, civil society organizations and researchers to embrace transformative approaches toward the agri-food system. Within this context, agroecology has emerged as a comprehensive methodology that aims to reshape food systems by harnessing the interconnectedness between indigenous knowledge, local conservation practices, social capital and strategies for adapting to the climate crisis. The pivotal role of women within agro-ecology is widely acknowledged, as their active engagement is considered crucial to the success and effectiveness of this approach. However, significant constraints persist in limiting women’s meaningful participation in agro-ecological farming systems, including constraints imposed by existing agricultural policies, institutional frameworks, gender roles, and limited access to markets, land, and information. Employing a gender and political-economy framework, this paper analyzes how agro-ecological approaches to agri-food systems have the potential to empower women, and where gaps and institutional barriers remain in limiting the participation of women. Through a comprehensive review of agriculture policy documents, case studies and empirical evidence, this study seeks to uncover the gaps and challenges in achieving gender-responsive policy and institutional frameworks within the agro-ecological context. By examining the intersectionality between gender, climate change, and food systems, this research contributes to a deeper understanding of the complex dynamics of the Indian agri-food systems and offers an alternative, inclusive paradigm to conventional systems of practice.